Evaluation of the Clinical Systems for Polymyxin Susceptibility Testing of Clinical Gram-Negative Bacteria in China - Zhu, Ying; Jia, Peiyao; Zhou, Menglan; Zhang, Jingjia; Zhang, Ge; Kang, Wei; Duan, Simeng; Wang, Tong; Xu, Yingchun; Yang, Qiwen (Frontiers in Microbiology, 2021)
Objectives: The performance of mainstream commercial antimicrobial susceptibility testing systems on polymyxins have not been well evaluated in China. In this study, three antimicrobial susceptibility testing systems were evaluated for polymyxin B and colistin. Methods: The MICs of 257 Gram-negative strains collected from clinical cases and livestock were determined and analyzed. Using Broth Microdilution as the gold standard, the performance of VITEK 2® COMPACT, Phoenix™ M50 and Bio-kont AST System were evaluated. Essential agreement (EA), category agreement (CA), very major error (VME) and major error (ME) were calculated for comparison. The results of mcr-1 positive strains were separately discussed. Results: The EA, CA, VME and ME to polymyxin B for Bio-kont were 83.5%, 95.6%, 13.1% and 0.6%, respectively. The EAs, CAs, VMEs and MEs to colistin were as follows: Bio-kont, 86.7%/96.5%/7.2%/1.7%; Vitek 2, 64.2%/86.8%/41.0%/0% and Phoenix M50, 92.9%/92.9%/21.7%/0%. The performance of Bio-kont to polymyxin B and colistin for Pseudomonas spp. (EA, CA <90%, VME >1.5%, ME=5.6%/10%) and Enterobacter spp. (EA, CA <90%, VME >1.5% and ME= 0%), Vitek to colistin for most genera and Phoenix to colistin for Enterobacter spp. (EA, CA <90%, VME >1.5%, ME=0%) were unsatisfactory compared with other genera. The performance of Bio-kont to polymyxins for Escherichia spp. and Phoenix to colistin for Citrobacter spp., Escherichia spp. and Klebsiella spp., which all met the CLSI standard, were satisfactory. When the susceptibility of mcr-1 positive E. coli was tested, Bio-kont and Phoenix M50 presented excellent performance with no category errors, while Vitek 2 performed a high VME (25.5%). Conclusions: With relatively more accurate results for polymyxin B and colistin and lower VME, Bio-kont has its advantage for polymyxin antimicrobial susceptibility testing, especially for Escherichia spp., Klebsiella spp., Citrobacter spp. and Acinetobacter spp..